Impulsivity and cognitive distortions in different clinical phenotypes of gambling disorder: Profiles and longitudinal prediction of treatment outcomes - Mallorquí-Bagué, Núria; Vintró-Alcaraz, Cristina; Verdejo-García, Antonio; Granero, Roser; Fernández-Aranda, Fernando; Magaña, Pablo; Mena-Moreno, Teresa; Aymamí, Neus; Gómez-Peña, Mónica; Del Pino-Gutiérrez, Amparo; Mestre-Bach, Gemma; Menchón, José M.; et al. (European psychiatry, 2019)
Impulsivity and cognitive distortions are hallmarks of gambling disorder (GD) but it remains unclear how they contribute to clinical phenotypes. This study aimed to (1) compare impulsive traits and gambling-related distortions in strategic versus non-strategic gamblers and online versus offline gamblers; (2) examine the longitudinal association between impulsivity/cognitive distortions and treatment retention and relapse. Participants seeking treatment for GD (n = 245) were assessed for gambling modality (clinical interview), impulsive traits (Urgency, Premeditation, Perseverance and Sensation Seeking [UPPS] scale) and cognitive distortions (Gambling Related Cognitions Scale) at treatment onset, and for retention and relapse (as indicated by the clinical team) at the end of treatment. Treatment consisted of 12-week standardized cognitive behavioral therapy, conducted in a public specialized clinic within a general public hospital. Strategic gamblers had higher lack of perseverance and gambling-related expectancies and illusion of control than non-strategic gamblers, and online gamblers had generally higher distortions but similar impulsivity to offline gamblers. Lack of perseverance predicted treatment dropout, whereas negative urgency and distortions of inability to stop gambling and interpretative bias predicted number of relapses during treatment. Individuals with online and strategic GD phenotypes have heightened gambling related biases associated with premature treatment cessation and relapse. Findings suggest that these GD phenotypes may need tailored treatment approaches to reduce specific distortions and impulsive facets.